Synaptic plasticity and preliminary-spike-enhanced plasticity in a CMOS-compatible Ta2O5 memristor - Hyun–Gyu Hwang; Jong–Un Woo; Tae–Ho Lee; Sung-Mean Park; Tae–Gon Lee; Woong-Hee Lee; Sahn Nahm (Materials & Design, 2020)
An artificial synapse that can perform both learning and memory functions was realized using an amorphous Ta2O5 memristor. A Pt/Ta2O5/TiN memristor, with an amorphous Ta2O5 film grown at 100 °C, exhibited reliable bipolar switching properties at the various conductance states required for artificial synapse applications; in addition, it exhibited the transmission properties of physiological synapses. Various other synaptic properties were also obtained from the Ta2O5 memristor by modulating the input bias. The metaplasticity of a physiological synapse, which is a preliminary-spike-enhanced synaptic function, was also emulated in the Ta2O5 memristor via the metaplasticity of potentiation/depression and spike-timing-dependent plasticity. The synaptic plasticity and metaplasticity of the Ta2O5 memristor can be understood via the construction and destruction of oxygen vacancy filaments in the memristor. Keywords: Amorphous Ta2O5 films, Memristor, Neuromorphic device, Artificial synapse, Synaptic plasticity, Metaplasticity